Severest crisis overlooked—Worst disruption of terrestrial environments postdates the Permian–Triassic mass extinction - Hochuli, Peter A. (Sci Rep, 2016)
Generally Early Triassic floras are believed to be depauperate, suffering from protracted recovery following the Permian–Triassic extinction event. Here we present palynological data of an expanded East Greenland section documenting recovered floras in the basal Triassic (Griesbachian) and a subsequent fundamental floral turnover, postdating the Permian–Triassic boundary extinction by about 500 kyrs. This event is marked by a swap in dominating floral elements, changing from gymnosperm pollen-dominated associations in the Griesbachian to lycopsid spore-dominated assemblages in the Dienerian. This turnover coincides with an extreme δ(13)C(org) negative shift revealing a severe environmental crisis, probably induced by volcanic outbursts of the Siberian Traps, accompanied by a climatic turnover, changing from cool and dry in the Griesbachian to hot and humid in the Dienerian. Estimates of sedimentation rates suggest that this environmental alteration took place within some 1000 years. Similar, coeval changes documented on the North Indian Margin (Pakistan) and the Bowen Basin (Australia) indicate the global extent of this crisis. Our results evidence the first profound disruption of the recovery of terrestrial environments about 500kyrs after the Permian–Triassic extinction event. It was followed by another crisis, about 1myrs later thus, the Early Triassic can be characterised as a time of successive environmental crises.